Fikrah Nahdliyah Dalam Membentuk Moral Bangsa; Studi Empiris Di PWNU Jawa Timur - Husnan, Ahmad Baihaqi (FAKULTAS TARBIYAH, 2021)
NU adopts Ahlussunah wal Jama'ah, a mindset that takes the middle path between the extremes aqli (rationalist) with the extreme naqli (scripturalist). Therefore, to reinforce identity, it was decided on a framework for the Nahdliyien which later became known as